One-Time Broadcast Encryption Schemes in Distributed Sensor Networks - Pawel Szalachowski; Zbigniew Kotulski (International Journal of Distributed Sensor Networks)
Broadcasting is a message-transferring method characteristic for majority of sensor networks. Broadcast encryption (BE) is broadcasting encrypted messages in such a way that only legitimate nodes of a network can decrypt them. It has many potential applications in distributed wireless sensor networks (WSNs) but perfect deploying of that method is very difficult. This is because of a WSN is a very dynamic network which includes nodes with limited computational, storage, and communication capabilities. Furthermore, an attacker in this environment is powerful. He can eavesdrop, modify, and inject messages or even capture a large number of nodes, so the solutions must be both secure and efficient. This paper describes several BE schemes from the point of view of WSNs. We present in details the schemes called onetime , and we show how these methods can be applied in distributed sensor networks. We mainly focus on data origin authentication and rekeying processes, crucial for security in such a hostile environment. An analysis and evaluations of proposed schemes are also provided.